PHONICS REVIEW Grades 2-3 - Henkel, Arlene; Boyer, Robin; Brooks, Nan; Hacker, Kathy; Strauss, Elizabeth (Michigan, USA School Zone Pub. Co, 1996)
For 20 years, School Zone I Know It! books have set the standard for home learning materials. Each book is developed by professional educators to complement the curriculum at each grade. Each I Know It! book has clear instructions and fun-to-do exercises
School Zone's I Know It! Reading workbooks are developed by teachers to support reading and phonics goals and objectives are each grade. Since this workbook is sequential, encourage your child to proceed from beginning to end. Use School Zone Workbook from a previous grade if your child need extra help or review. For enrichment or challenge, move ahead a grade or two
02008
Language and Languages
Linguistic Notions
2 12
Keywords: Alphabet; English language -- Alphabet